Hubungan Efikasi Diri dengan Kesiapan Kerja pada Siswa SMK - Ramadhan, Rahmat; Aulia, Farah (Lembaga Yasin AlSys, 2024)
As a provision for work, vocational high school students are required to have mature work readiness so that they can compete for the desired job. Job readiness for the workforce of vocational high school graduates is influenced by several factors, one of which is self-efficacy. This study aims to determine the relationship between self-efficacy and work readiness in vocational students. The method used in this research is quantitative method. In this study, the subjects were 323 SMKN students in Padang city. The data collection method in this study used a self-efficacy scale and a work readiness scale. Data analysis techniques using product moment correlation techniques. The results of hypothesis testing obtained a correlation coefficient value of 0.560 and a significance value of 0.000. This shows that there is a significant positive relationship between self-efficacy and work readiness in vocational students, meaning that the higher the self-efficacy of a student, the higher the work readiness of vocational high school students.